,,Bűncselekményt [...] vélt hazafiságból sem szabad elkövetni." Az oktobrista miniszterek nemzetrágalmazási perei - Drócsa Izabella (A Pázmány Péter Katolikus Egyetem Jog- és Államtudományi Karának Könyvei. Doktorandusz Tanulmányok, 2020)
After the downfall of the fi rst Communist Dictatory in Hungary, at the Horthyperiod the aggravation of the crimes against the state was suggested. That is why at the period of the fi rst government of Teleki the temporary parliament accepted the Act of Order No III of 1921 on the more eff ective protection of the state and social order (hereinafter referred to as the State Protection Act), which was applied to stop the radical political movements’s agitations. The 7. § of the State Protection Act regulated a special criminal act called libel against the nation. According to this fact of crime, it can be committed by stating false facts against the Hungarian state or the Hungarian nation. Those ministers who were in offi ce during the so-called People’s Republic in 1918-1919, maintained such a political activity abroad at the interwar, which suggested the suspicion of this crime. This article presents these criminal procedures.